Philometra sawara sp. n. and a redescription of Philometra sciaenae Yamaguti, 1941 and Philometra nemipteri Luo, 2001 (Nematoda: Philometridae): a morphological and molecular approach - Quiazon, Karl Marx A; Yoshinaga, Tomoyoshi; Ogawa, Kazuo (Folia parasitologica, 2008)
Morphological data and molecular analyses are used to describe the taxonomy of philometrid nematodes of the genus Philometra Costa, 1845, found in the gonads of marine fishes in Japan. A new Philomnetra species, P. sawara sp. n., is described based on male and female specimens collected from the gonads of Scomberomorus niphonius (Cuvier) (Japanese Spanish mackerel). Two additional species, Philometra nemipteri Luo, 2001 and Philometra sciaenae Yamaguti, 1941, are confirmed as valid species and are redescribed based on specimens collected from the gonads of Nemipterus virgatus (Houttuyn) (golden threadfin bream) and Pennahia argentata (Houttuyn) (silver croaker), respectively. Male P. nemipteri are first reported and described in this study. Redescriptions of female P. nemipteri and male and female P. sciaenae were also necessary based on our morphological observations. A molecular comparison of the internal transcribed spacer 2 (ITS2) region of the ribosomal DNA between P. sawara, P. nemipteri, P. sciaenae, and previously reported philometrid nematodes from the genus Philometra and Philometroides Yamaguti, 1935 supports the conclusion that the three Philometra species in the current study are independent. An ITS2-derived neighbour-joining tree, consisting of both the current specimens and previously described Philometra and Philometroides species, is also presented.
Keywords: Nematode Infections; Animals; Base Sequence; Nematoda; Seawater; Female; polymerázová řetězová reakce; Polymerase Chain Reaction; ženské pohlaví; Microscopy, Electron, Scanning; nemoci ryb; mikroskopie elektronová rastrovací; Gonads; nematodózy; Molecular Sequence Data; gonády; Fish Diseases; Fishes; Japonsko; ryby; mezerníky ribozomální DNA; DNA, Helminth; Japan; molekulární sekvence - údaje; hlístice; DNA helmintů; Male; Sequence Alignment; sekvence nukleotidů; Sequence Analysis, DNA; DNA, Ribosomal Spacer; mořská voda; zvířata; mužské pohlaví; sekvenční analýza DNA; sekvenční seřazení